2017
DOI: 10.1007/s00128-017-2100-z
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Analysis of Metal Concentrations in Two Fish Species of the Nyl River System, Limpopo Province, South Africa

Abstract: Increased toxicity due to high metal concentrations may hinder the ecological integrity of aquatic ecosystems in sustaining life. The non-biodegradable nature of metals may result in bioaccumulation in aquatic organisms. Due to ecological and social aspects it is imperative for monitoring schemes to identify possible impacts to the systems integrity. This paper discusses accumulation patterns of seven metals (Al, Cr, Cu, Fe, Mn, Sr and Zn) in tissues of two fish species, namely Clarias gariepinus and Oreochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…The concentration of Zn exceeded the recommended permissible limit of 30.0 mg/kg [27] in C. gariepinus and M. macrolepidotus at Site 2, O. mossambicus and L. rosae at Site 3, and S. zambezensis at Site 4. The recorded levels of Zn in various fish muscle tissues in this study are similar to other records from other South African rivers, such as the Sand River, Olifants River and Nyl River [41,42]. However, higher concentrations than the present study have been reported in O. mossambicus muscle tissues collected from Nyl River in the Limpopo Province [41].…”
Section: Zincsupporting
confidence: 89%
See 1 more Smart Citation
“…The concentration of Zn exceeded the recommended permissible limit of 30.0 mg/kg [27] in C. gariepinus and M. macrolepidotus at Site 2, O. mossambicus and L. rosae at Site 3, and S. zambezensis at Site 4. The recorded levels of Zn in various fish muscle tissues in this study are similar to other records from other South African rivers, such as the Sand River, Olifants River and Nyl River [41,42]. However, higher concentrations than the present study have been reported in O. mossambicus muscle tissues collected from Nyl River in the Limpopo Province [41].…”
Section: Zincsupporting
confidence: 89%
“…The recorded levels of Zn in various fish muscle tissues in this study are similar to other records from other South African rivers, such as the Sand River, Olifants River and Nyl River [41,42]. However, higher concentrations than the present study have been reported in O. mossambicus muscle tissues collected from Nyl River in the Limpopo Province [41]. The main sources of Zn could be from fertilizers [43] and sewage [44].…”
Section: Zincsupporting
confidence: 87%
“…The concept of trace element bioaccumulation in fish is well known [ 31 , 32 , 33 , 34 ]. Trace element levels in the Vaal Dam have been assessed in a number of studies and findings in the present work corroborate trends previously observed.…”
Section: Discussionmentioning
confidence: 99%
“…The use of fish and their attributes has proven to be successful in assessing the integrity and ecological status of aquatic ecosystems and identifying impacts affecting these systems for more than 25 years (Barbour et al 1999 ). An ideal fish species to use in South Africa is the sharptooth catfish, Clarias gariepinus due to the following: (i) large natural and introduced distribution (thus occurring in most South African river systems); (ii) wide tolerance to extreme environmental conditions; (iii) they are mostly associated with benthic feeding, are omnivorous and opportunistic feeders, and occupy high tropic levels; and (iv) most importantly is a valued food source for humans (Skelton, 2001 ; Picker and Griffiths 2011 ; Musa et al 2017 ; Froese and Pauly 2023 ). Their association with sediment and the feeding habits of C. gariepinus make them ideal representatives of element bioaccumulation (especially toxic elements) in aquatic systems, and with the fact that some elements can biomagnify through food webs, they can pose human health risks to communities chronically exposed to these toxic elements when they frequently consume polluted fish (Erasmus et al 2022b ).…”
Section: Introductionmentioning
confidence: 99%